Mengidentifikasi Dasar Algoritma Pemrograman - Erlianda Cibro; Yahfizham Yahfizham (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2024)
Programming algorithms are the basic principles when creating programs on a computer. Although closely related to mathematical calculations, real programming algorithms do not always involve complex calculations such as genetic algorithms which are usually used to solve mathematical problems. In analyzing an algorithm there are several parts that we can analyze, such as time speed, amount of cost, and amount of space. The 3 parts each use O (big O) notation. There is also Divided and Conquer. In this article the author uses a method, namely literature study. Below the author will present the basic steps of the programming algorithm